Method for producing lithium secondary battery containing perlithium manganese oxide
By using excess lithium manganese oxide in the manufacturing process of lithium secondary batteries and performing pressure charging and discharge activation, the problems of abnormal capacity increase and gas generation during the high-voltage activation process are solved, and the stability and life of the battery are improved.
Patent Information
- Application Number
- JP2024564601
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-12-20
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-12-20
AI Technical Summary
In the prior art, when manufacturing lithium secondary batteries containing excess lithium manganese oxide, there are problems of abnormal capacity increase and gas generation, especially during high-pressure activation.
When manufacturing a lithium secondary battery, excessive lithium manganese oxide is used as the positive electrode material and pressure charging and discharging activation is performed under the activation step. The charging mode includes constant current charging to a termination voltage and then converting to a constant voltage charging, and the charging termination voltage exceeds 4.35V.
It effectively suppresses abnormal capacity increase and gas generation during battery operation, and improves the stability and life of the battery.
Smart Images

Figure 2025514448000001_ABST
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0183684 filed on December 23, 2022, and all contents disclosed in the Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a method for producing a lithium secondary battery containing a perlithium manganese-based oxide, and more specifically, to a method for producing a lithium secondary battery containing a perlithium manganese-based oxide that can suppress abnormal capacity increase and gas generation during battery operation. [Background technology]
[0003] Lithium secondary batteries are energy storage media that have been applied in various fields since they were commercialized in 1991. As the market for products equipped with lithium secondary batteries expands, research into increasing the energy density of lithium secondary batteries is being actively conducted, and one of the most notable methods is the development of a positive electrode active material with a composition that can utilize more lithium than currently available.
[0004] As a positive electrode active material capable of utilizing more lithium, a perlithium-based transition metal oxide having a layered structure and a lithium to transition metal molar ratio exceeding 1 has been developed. Such a perlithium-based transition metal oxide can achieve high capacity by simultaneously utilizing not only the positive ion redox reaction (cation redox) of the transition metal but also the negative ion redox reaction (anion redox) using oxygen in the positive electrode structure. A representative perlithium-based transition metal oxide that is currently being actively researched is a perlithium manganese-based oxide having a lithium to transition metal molar ratio exceeding 1 and a manganese content of 50 mol % or more of the total transition metal. The perlithium manganese-based oxide has a structure in which LiMO2 (where M is a transition metal) having a layered structure and Li2MnO3 having a rock salt structure are mixed, and Li2MnO3 is activated by performing an activation process at a high voltage of 4.4 V or more to achieve high capacity. However, there are problems in that oxygen desorption occurs during such a high voltage activation process, excessive gas is generated, and transition metals such as manganese are eluted. If the activation voltage is lowered, the amount of gas generated during the activation process can be reduced, but in this case, the Li2MnO3 phase that remained in the crystal structure during the battery operation process is activated, which can cause abnormal behavior such as abnormal capacity increase and additional gas generation, which can lead to problems. Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made to solve such problems, and aims to provide a method for manufacturing a lithium secondary battery that uses a perlithium manganese-based oxide that can suppress abnormal capacity increase and gas generation during battery operation by activating the battery under specific conditions. [Means for solving the problem]
[0006] The present invention provides a method for producing a lithium secondary battery, comprising the steps of: preparing a battery cell including a positive electrode, a negative electrode, and an electrolyte, the battery cell including a perlithium manganese-based oxide in which the manganese content of all metals excluding lithium exceeds 50 mol % and the ratio of the number of moles of lithium to the number of moles of all metals excluding lithium (Li / Me) exceeds 1; and activating the battery cell by charging and discharging under pressure, wherein in the activation step, charging is performed in a constant current mode up to a charge end voltage and then in a constant voltage mode, and the charge end voltage exceeds 4.35 V.
[0007] At this time, the constant current mode charging may be performed to include at least a part of a potential flattening section that appears during the constant current mode charging, and the cutoff current during the constant voltage mode charging may be 0.01C to 0.5C.
[0008] As an example, in the activating step, the constant current mode charging can be performed from SOC60 to SOC100.
[0009] Alternatively, in the activation step, the charging step may include a first charging step of performing constant current charging at a first current rate, and a second charging step of performing constant current charging at a second current rate different from the first current rate, followed by constant voltage charging, where the first current rate and the second current rate may be independently 0.1C to 1.0C.
[0010] In this case, the first charging step can be performed until the SOC of the battery cell reaches 30-60, and the second charging step can be performed after the first charging step, that is, from SOC 30-60 until the SOC reaches 90-100.
[0011] On the other hand, the activation step is preferably performed while the battery cell is mounted in a jig and pressure is applied thereto.
[0012] Also, the step of activation can be performed while changing the pressurization pressure. For example, in the step of activation, charging can be performed under a relatively low pressurization pressure P1 until the SOC of the battery cell reaches 10 to 20, and then the pressurization pressure can be increased to perform charging under a relatively high pressurization pressure P2. The pressurization pressure P1 and the pressurization pressure P2 can satisfy the following formula (1).
[0013] Formula (1): 5P1 ≤ P2 ≤ 15P1
[0014] On the other hand, in the present invention, in the dQ / dV graph obtained by differentiating the graph of the voltage V measured while charging the battery cell to 4.6V and the battery charging capacity Q, the charging curve area in the voltage range of 4.3V to 4.6V is A, and in the dQ / dV graph obtained by differentiating the graph of the voltage V measured while charging the battery cell to the charging end voltage in the step of activating the battery cell and the battery charging capacity Q, the charging curve area in the voltage range of 4.3V to the charging end voltage is B. It is preferable to satisfy the following formula (2).
[0015] Formula (2): 0.5A ≤ B ≤ A
[0016] In the present invention, the over-lithium manganese-based oxide may be represented by the following chemical formula 1.
[0017] [Chemical formula 1] Li a Ni b Co c Mn d M e O2
[0018] In the chemical formula 1, 1 < a, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.1, 0.5 < d < 1.0, 0 ≤ e ≤ 0.2, and M can include one or more selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr. Preferably, 1.1 ≤ a ≤ 1.5, 0.1 ≤ b ≤ 0.4, 0 ≤ c ≤ 0.05, 0.5 < d ≤ 0.80, 0 ≤ e ≤ 0.1.
Brief Description of the Drawings
[0019] [Figure 1] 1 is a graph showing cycle characteristics of lithium secondary batteries activated by the methods of Examples 1 to 3 and Comparative Examples 1 to 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The terms or words used in this specification and the claims are not to be interpreted limited to their ordinary or dictionary meanings, but are to be interpreted in a meaning and concept that is consistent with the technical idea of the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.
[0021] In the present invention, the term "primary particles" refers to particle units that do not appear to have grain boundaries when observed at a magnification of 5,000 to 20,000 times using a scanning electron microscope. The term "average particle size of primary particles" refers to the arithmetic mean value calculated after measuring the particle sizes of primary particles observed in a scanning electron microscope image.
[0022] In the present invention, the "secondary particles" refer to particles formed by agglomeration of a plurality of primary particles.
[0023] In the present invention, the "average particle size D 50 " means the particle size at 50% of the volume cumulative particle size distribution of the particle powder to be measured (e.g., positive electrode active material powder, negative electrode active material powder, etc.). 50 can be measured using the laser diffraction method. For example, the powder of the particles to be measured is dispersed in a dispersion medium, then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and ultrasonic waves of about 28 kHz are irradiated at an output of 60 W. After obtaining a volume cumulative particle size distribution graph, the particle size corresponding to 50% of the volume cumulative amount can be measured.
[0024] In the present invention, "SOC X" means a state where the percentage of the capacity charged in a battery cell to the discharge capacity that appears when the battery cell is discharged from 4.6 V to 2.0 V (i.e., (charged capacity / discharge capacity of battery cell in the voltage range of 4.6 to 2.0 V) × 100) is X.
[0025] The present inventors have conducted extensive research to improve the phenomenon that the capacity of a lithium secondary battery using a perlithium manganese oxide increases abnormally and the amount of gas generated increases during operation. As a result, they have found that this can be improved by performing an activation process under specific conditions during the manufacture of a lithium secondary battery, and have completed the present invention.
[0026] The present invention will be specifically described below.
[0027] The method for producing a lithium secondary battery according to the present invention includes: (1) preparing a battery cell including a positive electrode, a negative electrode, and an electrolyte; and (2) activating the battery cell by charging and discharging the battery cell under pressure, wherein in the activation step, charging is performed in a constant current mode up to a charge cut-off voltage, and then charging is performed in a constant voltage mode, and the charge cut-off voltage is greater than 4.35 V.
[0028] (1) Prepare the battery cells First, a battery cell including a positive electrode, a negative electrode, and an electrolyte is prepared.
[0029] The battery cell may be manufactured by forming an electrode assembly including a positive electrode and a negative electrode, housing the electrode assembly in a battery case, injecting an electrolyte, and sealing the battery case, where the electrode assembly may include a separator between the positive electrode and the negative electrode.
[0030] The electrode assembly may be an electrode assembly of various types well known in the art, for example, a jelly roll type, a stack type, a stack and lamination type, or a stack and folding type, and the type is not particularly limited.
[0031] The jelly roll type electrode assembly can be manufactured by interposing a sheet-shaped separator between a sheet-shaped positive electrode and a sheet-shaped negative electrode, and then winding the electrodes in one direction.
[0032] The stacked electrode assembly can be manufactured by cutting the positive electrode, separator, and negative electrode into a desired shape, and then stacking the cut positive electrode / separator / negative electrode in sequence.
[0033] The stack-and-lamination type electrode assembly may be manufactured by stacking a positive electrode, a separator, and a negative electrode to manufacture a plurality of unit cells, stacking the plurality of unit cells with a separator interposed therebetween, and laminating the stacked unit cells by a method such as heating.
[0034] The stack-and-fold type electrode assembly may be manufactured by stacking a positive electrode, a separator, and a negative electrode to manufacture a plurality of unit cells, arranging the plurality of unit cells on one or both sides of a long folding separator, and then winding up the folding separator.
[0035] Meanwhile, as the battery case, various battery cases known in the art, such as a cylindrical battery case, a square battery case, or a pouch-type battery case, may be used, and the type is not particularly limited.
[0036] Meanwhile, the positive electrode according to the present invention includes, as a positive electrode active material, a perlithium manganese-based oxide in which the manganese content among all metals excluding lithium exceeds 50 mol % and the ratio of the number of moles of lithium to the number of moles of all metals excluding lithium (Li / Me) exceeds 1. Specifically, the positive electrode according to the present invention includes a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes a perlithium manganese-based oxide in which the ratio of the number of moles of lithium to the number of moles of all metals excluding lithium (Li / Me) exceeds 1.
[0037] In the case of a lithium-rich manganese-based oxide containing excess lithium, it has a structure in which a layered structure phase (LiM’O2) and a rock-salt structure phase (Li2MnO3) coexist. During the initial activation process, while the rock-salt structure phase is being activated, excess lithium ions are generated, enabling the realization of a high capacity.
[0038] Preferably, the lithium-rich manganese-based oxide can be represented by Chemical Formula 1.
[0039] [Chemical Formula 1] Li a Ni b Co c Mn d M e O2
[0040] In Chemical Formula 1, M can be one or more selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
[0041] On the other hand, a is the molar ratio of Li in the lithium-rich manganese-based oxide, and it may be 1 < a, 1.1 ≤ a ≤ 1.5, or 1.1 ≤ a ≤ 1.3. When a is within the above range, it can sufficiently compensate for the irreversible capacity of the silicon-based negative electrode active material, enabling the realization of high-capacity characteristics.
[0042] The b is the molar ratio of Ni in the lithium-rich manganese-based oxide, and it can be 0 ≤ b ≤ 0.5, 0.1 ≤ b ≤ 0.4, or 0.2 ≤ b ≤ 0.4.
[0043] The c is the molar ratio of Co in the lithium-rich manganese-based oxide, and it can be 0 ≤ c ≤ 0.1, 0 ≤ c ≤ 0.08, or 0 ≤ c ≤ 0.05. When c exceeds 0.1, it is difficult to ensure a high capacity, gas generation and degradation of the positive electrode active material become severe, and the life characteristics may deteriorate.
[0044] Said d is the molar ratio of Mn in the over-lithiated manganese-based oxide, and can be 0.5 < d < 1.0, 0.50 < d ≤ 0.80, or 0.50 < d ≤ 0.70. When d is less than 0.5, the ratio of the rock-salt type structure phase is too small, and the negative electrode irreversible compensation and capacity improvement effects are small.
[0045] Said e is the molar ratio of the doping element M in the over-lithiated manganese-based oxide, and can be 0 ≤ e ≤ 0.2, 0 ≤ e ≤ 0.1 or 0 ≤ e ≤ 0.05. If the content of the doping element is too high, it may have an adverse effect on the active material capacity.
[0046] On the other hand, in the over-lithiated manganese-based oxide represented by Chemical Formula 1, the molar ratio of Li to the total number of moles of all metal elements excluding Li (Li / Me) may be 1.2 - 1.5, 1.25 - 1.5, or 1.25 - 1.4. When the Li / Me ratio satisfies the above range, the rate characteristics and capacity characteristics are well manifested. If the Li / Me ratio is too high, the electrical conductivity may decrease, the rock-salt type structure phase (Li2MnO3) may increase, and the degradation rate may increase. If it is too low, the energy density improvement effect is negligible.
[0047] On the other hand, the composition of the over-lithiated manganese-based oxide can also be represented by the following Chemical Formula 2.
[0048] [Chemical Formula 2] XLi2MnO3·(1 - X)Li[Ni 1-y-z-w Mn y Co z M w O2
[0049] In Chemical Formula 2, M can be one or more selected from the group consisting of metal ions Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
[0050] The X means a ratio of the Li2MnO3 phase in the perlithium manganese-based oxide, and may be 0.2≦X≦0.5, 0.25≦X≦0.5, or 0.25≦X≦0.4. When the ratio of the Li2MnO3 phase in the perlithium manganese-based oxide satisfies the above range, the irreversible capacity of the silicon-based negative electrode active material can be sufficiently compensated, and high capacity characteristics can be achieved.
[0051] The y is a molar ratio of Mn in the LiM'O2 layer, and can be 0.4≦y<1, 0.4≦y≦0.8, or 0.4≦y≦0.7.
[0052] The z is a molar ratio of Co in the LiM'O2 layer, and may be 0≦z≦0.1, 0≦z≦0.08, or 0≦z≦0.05. If z exceeds 0.1, gas generation and degradation of the positive electrode active material become severe, and the life characteristics may be reduced.
[0053] The w is the molar ratio of the doping element M in the LiM'O2 layer, and can be 0≦w≦0.2, 0≦w≦0.1, or 0≦w≦0.05.
[0054] Meanwhile, the positive electrode active material according to the present invention may further include a coating layer on the surface of the perlithium manganese-based oxide, if necessary. When the positive electrode active material includes a coating layer, the coating layer inhibits contact between the perlithium manganese-based oxide and the electrolyte, thereby reducing electrolyte side reactions, thereby improving the life characteristics.
[0055] The coating layer is a coating element M 1 The coating element M 1 may be, for example, one or more selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr and Zr, preferably Al, Co, Nb, W and combinations thereof, more preferably Al, Co and combinations thereof. 1can contain two or more kinds, for example, can contain Al and Co.
[0056] The coating elements are in the oxide form in the coating layer, i.e., M 1 It can exist in Oz (1≦z≦4).
[0057] The coating layer can be formed by a method such as dry coating, wet coating, chemical vapor deposition (CVD), physical vapor deposition (PVD), atomic layer deposition (ALD), etc. Among these, the coating layer is preferably formed by an atomic layer deposition method, since it can form a coating layer with a large area.
[0058] The area of the coating layer formed may be 10 to 100%, preferably 30 to 100%, and more preferably 50 to 100% of the total surface area of the perlithium manganese oxide particles. When the area of the coating layer formed satisfies the above range, the effect of improving the life characteristics is excellent.
[0059] Meanwhile, the positive electrode active material according to the present invention may be in the form of secondary particles in which a plurality of primary particles are aggregated, and the average particle diameter D 50 The diameter of the positive electrode active material may be 2 μm to 10 μm, preferably 2 μm to 8 μm, and more preferably 4 μm to 8 μm. 50 When the above range is satisfied, the electrode density can be satisfactorily realized, and the deterioration of the capacity and rate characteristics can be minimized.
[0060] The positive electrode active material has a BET specific surface area of 1 m 2 / g~10m 2 / g, 3-8m 2 / g or 4~6m 2 If the BET specific surface area of the positive electrode active material is too low, the reaction area with the electrolyte is insufficient, making it difficult to achieve sufficient capacity, whereas if the specific surface area is too high, moisture absorption is rapid, accelerating side reactions with the electrolyte, making it difficult to ensure the life characteristics.
[0061] Meanwhile, the perlithium manganese oxide may be prepared by mixing a transition metal precursor and a lithium source material and then calcining the mixture.
[0062] Examples of the lithium source material include lithium-containing carbonates (e.g., lithium carbonate, etc.), hydrates (e.g., lithium hydroxide hydrate (LiOH·H2O), etc.), hydroxides (e.g., lithium hydroxide), nitrates (e.g., lithium nitrate (LiNO3), etc.), and chlorides (e.g., lithium chloride (LiCl)), and any one of these may be used alone or in combination of two or more.
[0063] Meanwhile, the transition metal precursor may be in the form of a hydroxide, oxide or carbonate. When a precursor in the form of a carbonate is used, it is more preferable in that a positive electrode active material having a relatively high specific surface area can be prepared.
[0064] The transition metal precursor may be prepared through a co-precipitation process. For example, the transition metal precursor may be prepared by dissolving each transition metal-containing raw material in a solvent to prepare a metal solution, mixing the metal solution, an ammonium cation complexing agent, and a basic compound, and then performing a co-precipitation reaction. If necessary, an oxidizing agent or oxygen gas may be further added during the co-precipitation reaction.
[0065] In this case, the transition metal-containing raw material may be acetate, carbonate, nitrate, sulfate, halogen compound, sulfide, etc. of each transition metal. Specifically, the transition metal-containing raw material may be NiO, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, Mn2O3, MnO2, Mn3O4, MnCO3, Mn(NO3)2, MnSO4·H2O, manganese acetate, manganese halide, cobalt sulfate, cobalt nitrate, cobalt carbonate, cobalt oxide, cobalt acetate, cobalt halide, etc.
[0066] The ammonium positive ion complexing agent can be one or more selected from the group consisting of NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, and NH4CO3.
[0067] The basic compound may be one or more selected from the group consisting of NaOH, Na2CO3, KOH, and Ca(OH)2. The form of the precursor may vary depending on the type of basic compound used. For example, when NaOH is used as the basic compound, a hydroxide-form precursor can be obtained, and when Na2CO3 is used as the basic compound, a carbonate-form precursor can be obtained. In addition, when a basic compound is used together with an oxidizing agent, an oxide-form precursor can be obtained.
[0068] Meanwhile, the transition metal precursor and the lithium source material can be mixed in amounts such that the molar ratio of total transition metals (Ni+Co+Mn):Li is 1:1.05 to 1:2, preferably 1:1.1 to 1:1.8, and more preferably 1:1.25 to 1:1.8.
[0069] Meanwhile, the firing can be carried out at a temperature of 600° C. to 1000° C. or 700° C. to 950° C., and the firing time can be 5 hours to 30 hours or 5 hours to 20 hours. The firing atmosphere can be an air atmosphere or an oxygen atmosphere, for example, an atmosphere containing 20 to 100 volume % oxygen.
[0070] Meanwhile, the positive electrode active material layer may further include a conductive material and a binder in addition to the positive electrode active material.
[0071] Examples of the conductive material include spherical or flaky graphite; carbonaceous materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, single-walled carbon nanotubes, and multi-walled carbon nanotubes; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these may be used alone or in combination. The conductive material may be included in an amount of 0.1 to 20% by weight, 1 to 20% by weight, or 1 to 10% by weight based on the total weight of the positive electrode active material layer.
[0072] Examples of the binder include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these can be used alone or in combination. The binder can be included in an amount of 1 to 20% by weight, 2 to 20% by weight, or 2 to 10% by weight based on the total weight of the positive electrode active material layer.
[0073] The negative electrode may include, for example, a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector. The negative electrode active material layer may include a negative electrode active material, and optionally a binder and a conductive material.
[0074] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3 to 500 μm, and like the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine irregularities on the surface of the current collector. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0075] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the above-mentioned metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these can be used.
[0076] Also, a metallic lithium thin film can be used as the negative electrode active material. Also, both low-crystalline carbon and high-crystalline carbon can be used as the carbon material. Typical low-crystalline carbons are soft carbon and hard carbon, and typical high-crystalline carbons are amorphous, plate-like, scaly, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbons such as petroleum or coal tar pitch derived cokes.
[0077] The conductive material is used to impart conductivity to the electrode, and can be used without any particular restrictions as long as it does not cause a chemical change in the battery that is constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and carbon nanotubes; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in mixture. The conductive material can usually be contained in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, and more preferably 1 to 10% by weight, based on the total weight of the negative electrode active material layer.
[0078] The binder plays a role in improving the adhesion between the negative electrode active material particles and the adhesive strength between the negative electrode active material and the negative electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these can be used alone or in combination. The binder can be included in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, more preferably 1 to 10% by weight, based on the total weight of the negative electrode active material layer.
[0079] The negative electrode active material layer can be manufactured, for example, by applying a negative electrode slurry containing a negative electrode active material, and optionally a binder and a conductive material, onto a negative electrode current collector and drying the applied slurry, or by casting the negative electrode slurry onto a separate support, peeling the negative electrode slurry from the support, and laminating the resulting film onto the negative electrode current collector.
[0080] Next, the separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator that is generally used in lithium secondary batteries can be used without any particular limitation, and in particular, a separator that has low resistance to ion movement of the electrolyte and excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric such as a high-melting glass fiber or a polyethylene terephthalate fiber, can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single layer or multilayer structure.
[0081] Next, the electrolyte may be any of various electrolytes that can be used in lithium secondary batteries, such as an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, or a combination thereof, and the type of the electrolyte is not particularly limited.
[0082] For example, the electrolyte can include an organic solvent and a lithium salt.
[0083] The organic solvent can be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move.Specific examples of the organic solvent include ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether solvents such as dibutyl ether and tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylenecarbonate (EC), and propylene carbonate (propylene carbonate). Examples of solvents that can be used include carbonate solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; and sulfolanes.
[0084] The lithium salt can be used without any particular limitation as long as it is a compound that can provide lithium ions used in lithium secondary batteries. Specifically, the negative ion of the lithium salt is F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , CF3CF2SO3 -, (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN- and (CF3CF2SO2)2N - The lithium salt may be LiPF6, LiN(FSO2)2, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. The concentration of the lithium salt is preferably within the range of 0.1 to 5.0M.
[0085] In addition to the above components, the electrolyte may further contain additives for the purpose of improving the life characteristics of the battery, suppressing the decrease in the battery capacity, and improving the discharge capacity of the battery. For example, the additives may be haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, which may be used alone or in combination, but are not limited thereto. The additives may be contained in an amount of 0.1 to 10% by weight, preferably 0.1 to 5% by weight, based on the total weight of the electrolyte.
[0086] (2) Activation step Next, the battery cell is electrically activated by charging and discharging it at least once under pressure. The activation step is a process in which the battery cell is charged and discharged to impart electrical properties and a solid electrolyte interphase (SEI) film is formed on the electrodes to stabilize the battery.
[0087] In the present invention, the charge and discharge in the activation process are performed under pressure. In this case, the pressurization can be performed, for example, by mounting the battery cell on a jig and then applying pressure to the battery cell through the jig. In the case of a battery cell using a perlithium manganese oxide, if an excess gas is generated during the activation process and the gas is not smoothly discharged, lithium deposition may be induced by gas trapping or activation may occur unevenly, resulting in a decrease in cell performance. Therefore, in the present invention, the activation process is performed under pressure to suppress the generation of gas trapping throughout the battery cell and to allow the electrolyte to be appropriately impregnated, thereby enabling the Li2MnO3 phase to be uniformly activated at high voltage, thereby preventing abnormal behavior during battery operation.
[0088] On the other hand, the pressure is 0.1 kgf / cm 2 ~10kgf / cm 2 , preferably 0.1 kgf / cm 2 ~8kgf / cm 2 , and more preferably 0.2 kgf / cm 2 ~7kgf / cm 2 When the pressurizing pressure condition satisfies the above range, damage to the battery cell can be prevented, and the effects of improving gas discharge and electrolyte impregnation can be more excellent.
[0089] Meanwhile, in the present invention, the activation process can be performed while changing the pressurizing pressure as necessary. For example, in the early stage of charging in the activation step (e.g., SOC 20 or less), pressurization is performed at a relatively low pressure to allow electrolyte to be abundantly present at the electrode interface and to allow the SEI film to be stably formed, and at the point where the amount of gas generated due to the film formation increases (e.g., after SOC 20), the pressurizing pressure can be increased to remove gas from the electrode interface while charging. Charging can be performed under a relatively high pressurizing pressure. When the activation process is performed while changing the pressurizing pressure in this way, it is possible to minimize deformation and damage of the battery cell due to pressurization, maximize the gas discharge effect, and perform charging at a relatively high current rate, thereby obtaining the effect of shortening the activation process time.
[0090] More specifically, in the activation step, charging is performed under an increased pressure P1 until the SOC of the battery cell reaches 10 to 20, and then charging is performed under an increased pressure P2. At this time, it is preferable that P1 and P2 satisfy the condition of the following formula 1.
[0091] Formula (1): 5P1≦P2≦15P1
[0092] When P1 and P2 satisfy the condition of the formula (1), the gas discharge effect can be maximized, charging can be performed at a relatively high current rate, and the activation process time can be shortened.
[0093] Meanwhile, the present invention is characterized in that, during charging in the activation process, charging is performed in a constant current mode up to the end-of-charge voltage, and then charging is performed in a constant voltage mode. By charging in a constant current / constant voltage mode as in the present invention, it is possible to minimize the amount of unactivated Li2MnO3 phase, thereby preventing abnormal behavior during battery operation.
[0094] In one example of the activation step, the battery is charged in a constant current mode until the battery reaches SOC60 to SOC100, and then charged in a constant voltage mode. The cut-off current during the constant voltage mode charging can be 0.01C to 0.5C, or 0.06C to 0.5C.
[0095] Meanwhile, in another example of the activation step, the cut-off current during the constant voltage mode charging can be 0.01 C to 0.15 C, preferably 0.03 C to 0.10 C, and more preferably 0.03 C to 0.06 C. If the constant voltage mode charging is terminated too early, the activation may not proceed sufficiently, whereas if it is terminated too late, the activation process time becomes long, which may cause a problem of a decrease in production rate.
[0096] The charge cut-off voltage during charging is more than 4.35 V, and may be, for example, 4.4 V to 4.8 V, 4.4 V to 4.7 V, 4.4 V to 4.6 V, or 4.5 V to 4.6 V. If the charge cut-off voltage is 4.35 V or less, Li2MnO3 is not sufficiently activated, making it difficult to achieve a high capacity, and there is a possibility that abnormal behavior will occur in which the capacity increases during battery operation.
[0097] Meanwhile, the constant current charging is preferably performed so as to include at least a part of the plateau potential section (4.4V to 4.6V). In the case of a battery using a perlithium manganese oxide, a plateau potential section where the voltage is relatively constant appears in the voltage range of 4.4V to 4.6V in the voltage profile according to the charging rate. When the constant current charging is performed so as to include at least a part of the plateau potential section, the perlithium manganese oxide is activated and high capacity characteristics can be realized. When the plateau potential section is not included during the activation charging, the Li2MnO3 phase is not sufficiently activated, so that the capacity increase effect is small and abnormal behavior may occur during cycle execution.
[0098] More specifically, the end-of-charge voltage can be set so as to satisfy the following formula (2).
[0099] Formula (2): 0.5A≦B≦A
[0100] In the formula (2), A is the charging curve area in the voltage range of 4.3V to 4.6V on a dQ / dV graph obtained by differentiating a graph of the voltage V and battery charge capacity Q measured while charging the battery cell to 4.6V, and B is the charging curve area in the voltage range of 4.3V to the charge end voltage on a dQ / dV graph obtained by differentiating a graph of the voltage V and battery charge capacity Q measured while charging the battery cell to the charge end voltage in the activation step.
[0101] When the end-of-charge voltage during activation charging is set to satisfy the formula (2), high-voltage activation is sufficiently performed, the capacity is excellent, and the occurrence of abnormal behavior due to non-uniform activation of the Li2MnO3 phase can be more effectively suppressed.
[0102] Meanwhile, the charging may include two or more steps with different charging rates, if necessary. For example, the charging may include a first charging step of performing constant current charging at a first current rate, and a second charging step of performing constant current charging at a second current rate different from the first current rate, followed by constant voltage charging.
[0103] In this case, the first current rate and the second current rate may be independently set to 0.1C to 1.0C, or 0.1C to 0.8C, or 0.2C to 0.8C, or 0.3C to 0.6C.
[0104] Preferably, the first current rate may be smaller than the second current rate. That is, the first charging step may be performed at a relatively low rate, and the second charging step may be performed at a relatively high rate. If the current rate is high in the first charging step, the SEI film may be formed unstably on the electrode surface. If the SEI film is formed unstably on the electrode surface, the SEI film may be easily decomposed during battery operation, causing rapid degradation of the electrode, and thus the life characteristics may be significantly reduced. However, if the charging rate is too slow, there is a problem that the total time of the activation process increases and the production rate decreases. However, as in the present invention, the first charging step, which is the initial charging step in which the SEI film is formed, is charged at a low rate, and the second charging step, which is after the SEI film has been formed to a certain extent, is charged at a high rate, so that the SEI film can be stably formed on the electrode surface while the total time of the activation process can be reduced.
[0105] Meanwhile, the first charging step can be performed until the SOC of the battery cell reaches 30 to 60. When the charging capacity in the first charging step satisfies the above range, a strong and dense SEI film is formed on the electrode surface, and excellent life characteristics can be achieved.
[0106] Meanwhile, the first charging step may be performed in two or more steps with different rate limits, as necessary. For example, the first charging step may include a 1-1 charging step of charging the battery cell at a C rate of 0.1C to 0.3C, and a 1-2 charging step of charging the battery cell at a C rate of 0.3C to 1.0C. In this case, the 1-1 charging step may be performed from SOC0 to SOC3 to 5, and the 1-2 charging step may be performed from SOC3 to 5 to SOC30 to 60. When the first charging step is performed in two steps as described above, the charging rate can be further lowered in the initial stage of SEI film formation, and a stronger and denser SEI film can be formed, and then, by increasing the charging rate, the occurrence of oxygen desorption and positive ion mixing can be suppressed, and the time required for the activation process can be shortened.
[0107] Meanwhile, the second charging step is preferably performed after the first charging step, i.e., from SOC 30-60 to SOC 90-100. When the charging capacity in the second charging step satisfies the above range, it is possible to suppress incomplete formation of the SEI film, sufficiently activate Li2MnO3, and effectively prevent abnormal behavior during battery operation.
[0108] The second charging step is performed in a constant current constant voltage mode, and the current rate (C rate) during the constant current charging can be 0.1C to 1.0C, more preferably 0.3C to 0.8C, and even more preferably 0.3C to 0.6C.
[0109] Next, the charged battery cell is discharged. At this time, the discharge can be performed at a C rate of 0.1 C to 1 C, preferably 0.3 to 1 C. Meanwhile, the discharge can be performed in a constant current mode (CC mode), and the discharge cut-off voltage can be 2.0 V to 3.0 V.
[0110] On the other hand, the activation step is preferably carried out at a temperature condition of 25° C. to 70° C., preferably 30° C. to 60° C., and more preferably 40° C. to 50° C. When the activation step is carried out in the above temperature range, Li2MnO3 is appropriately activated, and a high capacity can be achieved.
[0111] Meanwhile, if necessary, but not necessarily, the activation step may further include an aging step, which is for the purpose of allowing the electrolyte to uniformly impregnate the electrode assembly and stabilizing the battery, and may be performed before, during, and / or after charging, and may be performed one or more times.
[0112] The aging step can be carried out at a temperature of, for example, 20° C. to 60° C., 20° C. to 50° C., and preferably 30° C. to 50° C. When aging is carried out at the above temperatures, electrolyte impregnation and lithium mobility are improved, and activation can be carried out more smoothly.
[0113] The present invention will be described in more detail with reference to the following specific examples.
[0114] Example 1 The positive electrode active material, conductive material, and PVDF binder were mixed in a weight ratio of 97:1:2 in N-methylpyrrolidone to prepare a positive electrode slurry. 1.38 [Ni 0.363 Co 0.005 Mn 0.642 ]O2 was used as the cathode material, and CNT was used as the conductive material. The cathode slurry was applied onto an aluminum collector sheet, dried, and then rolled to produce a cathode.
[0115] Anode active material:conductive material:binder were mixed in water in a weight ratio of 96:1:3 to prepare anode slurry. Graphite was used as the anode active material, carbon black as the conductive material, and SBR and CMC were mixed in a weight ratio of 2:1 to prepare a binder. The anode slurry was applied onto a copper current collector sheet, dried, and then rolled to prepare anode.
[0116] A separator was interposed between the positive and negative electrodes to prepare an electrode assembly, and the electrode assembly was inserted into a battery case and an electrolyte was injected to prepare a battery cell.
[0117] The battery cell was attached to a jig and charged to 4.6 V in 0.3 C constant current mode, then changed to constant voltage mode and charging was continued, and charging was terminated when the current reached 0.05 C. Next, the charged battery cell was discharged to 2.0 V at a constant current of 0.5 C, and then the battery cell was removed from the jig. Meanwhile, during the charging, the discharge current was 0.5 kgf / cm from SOC 0 to 17. 2 After that, the jig was adjusted to a pressure of 5kgf / cm 2 Charging and discharging were carried out while applying a pressure of 1000 psi.
[0118] Example 2 A battery cell was manufactured in the same manner as in Example 1, and the manufactured battery cell was attached to a jig and then charged in a 1.0C constant current mode to SOC60 (first charging step). Thereafter, charging was performed in a 0.4C constant current mode to 4.6V, and then charging was performed in a constant voltage mode, and charging was terminated when the current reached 0.05C (second charging step). Thereafter, the charged battery cell was discharged to 2.0V at a constant current of 0.5C, and then the battery cell was removed from the jig. Meanwhile, during the charging, a 0.5kgf / cm 2 After that, the jig was adjusted to a pressure of 5kgf / cm 2 Charging and discharging were carried out while applying a pressure of 1000 psi.
[0119] Example 3 A battery cell was manufactured in the same manner as in Example 1, and the manufactured battery cell was attached to a jig and charged to 4.5 V in 0.3 C constant current mode, and then changed to constant voltage mode for charging, and charging was terminated when the current reached 0.05 C. Next, the charged battery cell was discharged to 2.0 V at a constant current of 0.5 C, and then the battery cell was removed from the jig. Meanwhile, during the charging, the discharge current was 0.5 kgf / cm from SOC 0 to 17. 2 After that, the jig was adjusted to a pressure of 5kgf / cm 2 Charging and discharging were carried out while applying a pressure of 1000 psi.
[0120] Comparative Example 1 A battery cell was manufactured in the same manner as in Example 1, and the manufactured battery cell was charged to 4.6 V in a 0.3 C constant current mode without being attached to a jig, and then the mode was changed to a constant voltage mode for charging, and charging was terminated when the current reached 0.05 C. The charged battery cell was then discharged to 2.0 V at a constant current of 0.5 C.
[0121] Comparative Example 2 A battery cell was manufactured in the same manner as in Example 1, and the manufactured battery cell was attached to a jig and charged to SOC60 in 1.0C constant current mode. Then, it was charged to 4.6V in 0.4C constant current mode. Then, the charged battery cell was discharged to 2.0V at a constant current of 0.5C, and then the battery cell was removed from the jig. Meanwhile, during the charging, the discharge current was 0.5kgf / cm from SOC0 to 17. 2 After that, the jig was adjusted to a pressure of 5kgf / cm 2 Charging and discharging were carried out while applying a pressure of 1000 psi.
[0122] Comparative Example 3 A battery cell was manufactured in the same manner as in Example 1, and the manufactured battery cell was attached to a jig and charged to 4.35 V in 0.3 C constant current mode, and then changed to constant voltage mode for charging, and charging was terminated when the current reached 0.05 C. Thereafter, the charged battery cell was discharged to 2.0 V at a constant current of 0.5 C, and then the battery cell was removed from the jig. Meanwhile, during the charging, the discharge current was 0.5 kgf / cm from SOC 0 to 17. 2 After that, the jig was adjusted to a pressure of 5kgf / cm 2 Charging and discharging were carried out while applying a pressure of 1000 psi.
[0123] Comparative Example 4 A battery cell was manufactured in the same manner as in Example 1, and the manufactured battery cell was attached to a jig and charged to 3.9 V in 0.3 C constant current mode, and then changed to constant voltage mode for charging. After that, the charged battery cell was discharged to 2.0 V at a constant current of 0.5 C, and then the battery cell was removed from the jig. Meanwhile, during the charging, the discharge current was 0.5 kgf / cm from SOC 0 to 17. 2 After that, the jig was adjusted to a pressure of 5kgf / cm 2 Charging and discharging were carried out while applying a pressure of 1000 psi.
[0124] Experimental Example 1 In the activation step of each of Examples 1 to 3 and Comparative Examples 1 to 4, the capacity was measured according to the voltage during the charging process, and a voltage-capacity graph was obtained. The voltage-capacity graph was differentiated to obtain a dQ / dV graph.
[0125] Thereafter, the percentages of the charge curve areas in the voltage range of 4.3 V to 4.6 V appearing in the dQ / dV graphs of Example 2 and Comparative Examples 1 to 4 were measured based on the charge curve areas in the voltage range of 4.3 V to 4.6 V appearing in the dQ / dV graphs of Example 1. The measurement results are shown in Table 1 below.
[0126] [Table 1]
[0127] Experimental Example 2: Initial Capacity The lithium secondary batteries activated according to the methods of Examples 1 to 3 and Comparative Examples 1 to 4 were charged to 4.35 V at 25° C., 0.33 C, in a constant current constant voltage mode, and then cut off when the current reached 0.05 C. Thereafter, the batteries were discharged to 2.0 V at a constant current of 0.33 C, and the initial discharge capacity was measured. When the initial discharge capacity of the lithium secondary battery of Example 1 was taken as 100%, the relative ratios of the initial discharge capacities of the lithium secondary batteries of Example 2 and Comparative Examples 2 to 5 were measured. The measurement results are shown in Table 2 below. On the other hand, the lithium secondary battery activated according to the method of Comparative Example 1 had Li plating, and the battery could not be driven.
[0128] [Table 2]
[0129] As shown in Table 2, the lithium secondary batteries of Examples 1 to 3, which were activated by charging to a voltage of 4.3 V or higher in a constant current / constant voltage mode while applying pressure using a jig, showed superior initial capacity compared to Comparative Examples 1 to 4. In contrast, the lithium secondary battery of Comparative Example 1, which was activated without applying pressure, was unable to operate as a battery due to the occurrence of lithium plating, and it was confirmed that the initial discharge capacity was reduced when charging was performed only in a constant current mode, not in a constant current / constant voltage mode, even including a pressure step (Comparative Example 2), or when activation was performed at a charge cut-off voltage of 4.35 V or lower (Comparative Examples 3 and 4).
[0130] Experimental example 3: High temperature life characteristics The lithium secondary batteries activated by the methods of Examples 1 to 3 and Comparative Examples 1 to 4 were charged to 4.35 V at 45° C. in a constant current / constant voltage mode (cutoff current 0.05 C) at 0.33 C, and then discharged to 2.0 V at a constant current of 0.33 C, which constitutes one cycle. After 50 charge / discharge cycles, the capacity retention rate and the voltage drop were measured. The measurement results are shown in FIG.
[0131] On the other hand, in the lithium secondary battery activated by the method of Comparative Example 1, Li plating occurred, and the battery could not be driven.
[0132] As shown in FIG. 1, the lithium secondary batteries activated by the methods of Examples 1 to 3 maintained a constant capacity and did not significantly increase in voltage drop during 50 charge / discharge cycles, whereas the lithium secondary batteries activated by the methods of Comparative Examples 2 to 4 exhibited abnormal operation in which the capacity increased with the increase in cycles and the voltage drop increased significantly. [Industrial Applicability]
[0133] In the method for manufacturing a lithium secondary battery according to the present invention, an activation process is performed under pressure and charging is performed in a constant current and constant voltage mode, which facilitates gas discharge and minimizes the non-activated Li2MnO3 phase, thereby preventing lithium precipitation and abnormal behavior during battery operation.
Claims
1. providing a battery cell including a positive electrode, a negative electrode, and an electrolyte, the positive electrode and the electrolyte including a perlithium manganese-based oxide having a manganese content of more than 50 mol % of all metals other than lithium and a ratio of the number of moles of lithium to the number of moles of all metals other than lithium (Li / Me) of more than 1; Activating the battery cell by charging and discharging under pressure; In the activation step, the charging is performed in a constant current mode until a charge end voltage is reached, and then in a constant voltage mode, so that the charge end voltage exceeds 4.35 V.
2. The method for producing a lithium secondary battery according to claim 1 , wherein the charging in the constant current mode is performed so as to include at least a part of a plateau potential section.
3. The lithium manganese oxide is represented by the following formula 1: [Chemical formula 1] Li a Ni b Co c Mn d M e O 2 2. The method of claim 1, wherein in Formula 1, 1<a, 0≦b≦0.5, 0≦c≦0.1, 0.5<d<1.0, 0≦e≦0.2, and M is at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
4. 4. The method for producing a lithium secondary battery according to claim 3, wherein, in Chemical Formula 1, 1.1≦a≦1.5, 0.1≦b≦0.4, 0≦c≦0.05, 0.5<d≦0.80, and 0≦e≦0.
1.
5. 2. The method for producing a lithium secondary battery according to claim 1, wherein the cutoff current during charging in the constant voltage mode is 0.01 C to 0.5 C.
6. 6. The method for producing a lithium secondary battery according to claim 5, wherein in the activation step, charging in the constant current mode is performed from SOC 60 to SOC 100.
7. 2. The method for producing a lithium secondary battery according to claim 1, wherein in the activation step, the charging includes a first charging step of performing constant current charging at a first current rate, and a second charging step of performing constant current charging at a second current rate different from the first current rate, and then performing constant voltage charging.
8. 8. The method for producing a lithium secondary battery according to claim 7, wherein the first current rate and the second current rate are each independently 0.1C to 1.0C.
9. 8. The method for manufacturing a lithium secondary battery according to claim 7, wherein the first charging step is performed up to an SOC of 30 to 60, and the second charging step is performed from an SOC of 30 to 60 to an SOC of 90 to 100.
10. The method for producing a lithium secondary battery according to claim 1 , wherein the activating step is performed while the battery cell is mounted on a jig and pressurized.
11. The method for producing a lithium secondary battery according to claim 1 , wherein the activation step is performed while changing the pressurizing pressure.
12. The activation step is performed by applying a pressurizing pressure P 1 Charging is performed under the pressure P 2 The method for producing a lithium secondary battery according to claim 1 , wherein charging and discharging are carried out under an atmospheric pressure.
13. The pressurized pressure P 1 and the pressurized pressure P 2 satisfies the following formula (1), Formula (1): 5P 1 ≦P 2 ≦15P 1 The method for producing a lithium secondary battery according to claim 12,
14. In a dQ / dV graph obtained by differentiating a graph of the voltage V and the battery charge capacity Q measured while charging the battery cell to 4.6 V, the area of the charge curve in the voltage range of 4.3 V to 4.6 V is A, and in a dQ / dV graph obtained by differentiating a graph of the voltage V and the battery charge capacity Q measured while charging the battery cell to the charge end voltage in the activation step, the area of the charge curve in the range of 4.3 V to the charge end voltage is B. Formula (2): 0.5A≦B≦A The method for producing a lithium secondary battery according to claim 1 ,
Citation Information
Patent Citations
Lithium ionic cell formation processing method
CN101308943A
Battery cell activation method and battery cell manufacturing method comprising same
EP4064400A1
Positive electrode active material for lithium ion secondary battery, lithium ion secondary battery including the positive electrode active material, and method for producing lithium manganese silver complex oxide
JP2013037879A
Positive electrode active material for nonaqueous secondary battery, positive electrode for nonaqueous secondary battery, nonaqueous secondary battery, and on-vehicle nonaqueous secondary battery module
JP2016051504A
Lithium metal secondary battery and battery module including the same
US20190341647A1